Biotechnology and security threats: National responses and prospects for international cooperation - Hanzhi Yu; Xue Yang (Centre for International Governance Innovation (CIGI), 2021)
Cutting-edge biotechnology, mainly consisting of gene editing, gene drives and gene synthesis, is developing and changing rapidly. It acts as a double-edged sword, bringing benefits to human development in many fields, such as medical treatment and agriculture, while also posing serious threats to biological security, human existence and development. For example, the case of He Jiankui, a young scholar from the Southern University of Science and Technology of China who created gene-edited babies, triggered a global controversy and debate on biosafety in the winter of 2018. This paper argues that the problems China faces do not only exist in China - they are in fact common problems faced by all countries in the world. Due to the COVID-19 pandemic, the world is paying close attention to global health governance and biosafety issues. There is a window of opportunity for global collaboration to deal with biosecurity threats.
Keywords: 330; Biotechnology; Product Safety; Coronavirus; Good Governance; China; Biotechnologie; Produktsicherheit; Coronavirus; Good Governance; China; Welt